2022
DOI: 10.1002/aenm.202200262
|View full text |Cite
|
Sign up to set email alerts
|

Highly Efficient (>9%) Lead‐Free AgBiS2 Colloidal Nanocrystal/Organic Hybrid Solar Cells

Abstract: Environmentally friendly colloidal nanocrystals (NCs) are promising materials for next‐generation solar cells because of their low cost, solution processability, and facile bandgap tunability. Recently, silver bismuth disulfide (AgBiS2) has attracted considerable attention owing to its appreciable power conversion efficiency (PCE) of 6.4%. However, issues such as the low open‐circuit voltage (VOC) compared to the bandgap of the AgBiS2 NCs and the unoptimized energy level structure at the AgBiS2 NC/PTB7 hole‐tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(31 citation statements)
references
References 25 publications
0
31
0
Order By: Relevance
“…The group further developed AgBiS 2 QD inks with 3-mercaptopropionic ligands, which can process with environment-friendly water, resulting in a PCE of 7.3% with a PTAA interface layer. 56 A recent work by Lee's group revealed that the performance of the AgBiS 2 QD/organic hybrid solar cells can be also enhanced by introducing PM6:BTP-4Cl blend. They employed the commonly used ligands, tetramethylammonium iodide and 2-mercaptoethanol, to provide the great passivation of AgBiS 2 QDs, which could deliver a high PCE of ∼9.1% (Fig.…”
Section: Bulk-heterojunctionmentioning
confidence: 99%
See 2 more Smart Citations
“…The group further developed AgBiS 2 QD inks with 3-mercaptopropionic ligands, which can process with environment-friendly water, resulting in a PCE of 7.3% with a PTAA interface layer. 56 A recent work by Lee's group revealed that the performance of the AgBiS 2 QD/organic hybrid solar cells can be also enhanced by introducing PM6:BTP-4Cl blend. They employed the commonly used ligands, tetramethylammonium iodide and 2-mercaptoethanol, to provide the great passivation of AgBiS 2 QDs, which could deliver a high PCE of ∼9.1% (Fig.…”
Section: Bulk-heterojunctionmentioning
confidence: 99%
“…Recently, AgBiS 2 QD solar cells have made a breakthrough in photovoltaic performance from ∼6.0% to over 9.0% with great passivation and the matched organic semiconductors. 56,59 Nevertheless, the performance still lags far behind those of PbS and perovskite QD counterparts, mainly stemming from high energy loss. More efforts should be devoted to improving the passivation of AgBiS 2 QDs and developing favorable organic HTLs.…”
Section: Agbis 2 Qd/organicmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, by adopting PBDB-T-2F:BTP-4Cl as a hole transport layer to obtain high J sc , the AgBiS 2 power conversion efficiency reaches 9.1%. 57 Since 2013, researchers have improved the device efficiency by adjusting the preparation process of AgBiS 2 NCs and optimizing the device structure. According to our review of the literature, AgBiS 2 thin film solar cells prepared by the SILAR method are one of the most effective devices with a breakthrough efficiency since no ligand exchange is involved.…”
Section: New Atfscs: Materials and Devicesmentioning
confidence: 99%
“…In addition, by adopting PBDB-T-2F:BTP-4Cl as a hole transport layer to obtain high J sc , the AgBiS 2 power conversion efficiency reaches 9.1%. 57…”
Section: New Atfscs: Materials and Devicesmentioning
confidence: 99%